An updated patent review of monoacylglycerol lipase (MAGL) inhibitors (2018-present). (1st February 2021) - Bononi, Giulia; Poli, Giulio; Rizzolio, Flavio; Tuccinardi, Tiziano; Macchia, Marco; Minutolo, Filippo; Granchi, Carlotta
ABSTRACT: Introduction: Monoacylglycerol lipase (MAGL) belongs to the endocannabinoid system and is responsible for the inactivation of endocannabinoid 2-arachidonoylglycerol. Importantly, it was found that MAGL degradation of lipids in cancer cells enhances the availability of free fatty acids for new cellular membrane formation and pro-oncogenic lipid modulators. The multifaceted role of MAGL has greatly stimulated the search for MAGL inhibitors, which could be effective to treat diseases, such as inflammation, neurodegeneration and cancer. Areas covered: This review covers patents published since 2018 up to now, concerning new MAGL inhibitors and their potential therapeutic applications. Expert opinion: In the years 2018–2020, several well-known chemical scaffolds of MAGL inhibitors have been further optimized and developed and some new chemical classes have also been identified as MAGL inhibitors. Moreover, an increasing number of scientific publications covering MAGL inhibitors is focused on MAGL-specific positron emission tomography (PET) ligands. The numerous efforts of pharmaceutical companies and academic research groups finalized to find new potent MAGL inhibitors confirm that this research area is rapidly growing. Nevertheless, most of the patented compounds still belong to the large group of irreversible MAGL inhibitors, highlighting that the development of reversible MAGL inhibitors is still an unmet pharmaceutical need.